(untitled) (Innovative professional education, 2022)
The categories of pedagogical workers within the dual system of vocational education in Germany are described. The peculiarities of the activity of pedagogical workers in the vocational school and at the enterprise are revealed. It is concluded that the positive experience of pedagogical workers of vocational education in Germany can be used to improve the professional development of teachers of VET in Ukraine.